Serum-Associated Antibiotic Tolerance in Pediatric Clinical Isolates of Pseudomonas aeruginosa. (30th December 2019) - Morrison, John M; Chojnacki, Michaelle; Fadrowski, Jeffrey J; Bauza, Colleen; Dunman, Paul M; Dudas, Robert A; Goldenberg, Neil A; Berman, David M
Abstract: Background: When grown in human serum, laboratory isolates of Pseudomonas aeruginosa exhibit tolerance to antibiotics at inhibitory concentrations. This phenomenon, known as serum-associated antibiotic tolerance (SAT), could lead to clinical treatment failure of pseudomonal infections. Our purpose in this study was to determine the prevalence and clinical impact of SAT in Pseudomonas isolates in hospitalized children. Methods: The SAT phenotype was assessed in patients aged <18 years admitted with respiratory or blood cultures positive for P. aeruginosa. The SAT phenotype was a priori defined as a ≥2-log increase in colony-forming units when grown in human serum compared with Luria-Bertani medium in the presence of minocycline or tobramycin. Results: SAT was detected in 29 (64%) patients. Fourteen patients each (34%) had cystic fibrosis (CF) and tracheostomies. Patient demographics and comorbidities did not differ by SAT status. Among CF patients, SAT was associated with longer duration of intravenous antibiotics (10 days vs 5 days; P < .01). Conclusions: This study establishes that SAT exists in P. aeruginosa from human serum and may be a novel factor that contributes to differences in clinical outcomes. Future research should investigate the mechanisms that contribute to SAT in order to identify novel targets for adjunctive antimicrobial therapies. Abstract : When grown in human serum, laboratory isolates of Pseudomonas aeruginosa exhibit tolerance to antibiotics (serum-associated antibiotic tolerance [SAT]). SAT was detected in two-thirds of P. aeruginosa from pediatric patients and may be a novel factor that contributes to differences in clinical outcomes.